Diagnostic Signals on Board Vessels with Dynamic Positioning System - Dęsoł, M. (Scientific Journal of Gdynia Maritime University, 2018)
The article presents the issues related to the analysis of signals monitoring the operation of ship equipment. Monitoring systems, purpose of their application and functions are briefly discussed. Signals used in monitoring and control systems of the ship power plant using additional, more detailed analysis can be used for additional diagnostic systems. The article presents research done in the real state of the ship system operation. Focus has been put on characterizing damages of sensors or devices. The problems of poor interpretation of failure symptoms by the operator and the alarm system were discussed.